Evidence that the catenane form of CS2 hydrolase is not an artefact. - van Eldijk, M; van Leeuwen, I; Mikhailov, V; Neijenhuis, L; Harhangi, H; van Hest, J; Jetten, MS; Op den Camp, H; Robinson, C; Mecinović, J (2013)
CS2 hydrolase, a zinc-dependent enzyme that converts carbon disulfide to carbon dioxide and hydrogen sulfide, exists as a mixture of octameric ring and hexadecameric catenane forms in solution. A combination of size exclusion chromatography, multi-angle laser light scattering, and mass spectrometric analyses revealed that the unusual catenane structure is not an artefact, but a naturally occurring structure.